The Rosetta Stone Italiano. - Fairfield Language Technologies (Firm). (Harrisonburg, VA : Fairfield Language Technologies, 2002)
A comprehensive language learning solutions for private, educational and professional use. With complete curriculum management, networking and record-keeping capabilities.
Keywords: Italian language -- Study and teaching -- Foreign speaker